Answer :

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c


For the given equation



=


And either of their sum or difference = b


=


Thus the two terms are


Difference =


Product = using








Hence roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses